The Integration of Departments with Ministries : Report of the Committee appointed to consider the integration of Departments with ministries, with a foreword by the Prime Minister of the Federation - NIGERIA (Lagos : Federal Republic of Nigeria, 1959)
The Federal government has been concerned with the question of the integration of Department with ministries. To this end it sought advice on the practice in the United Kingdom and a committee was formed to examine the matter. This is the Report of the Committee appointed to consider the integration of Departments with ministries, with a foreword by the Prime Minister of the Federation.
nmn, 23/04/19
Ref
Keywords: Ministries; Government departments; Ministries - integration; Nigeria